Incidence and causes of neonatal hyperbilirubinemia in a center of Catania - Marco Sciuto; Gaetano Bertino; Mariangela Zocco; Ignazio Vecchio; et al (Dove Medical Press, 2009)
Marco Sciuto1, Gaetano Bertino2, Mariangela Zocco3, Ignazio Vecchio4, Rocco Raffaele4, Rosario R Trifiletti5, Piero Pavone3,61Neonatal Care Section, Valsalva Hospital, Catania, Italy; 2Department of Internal Medicine, Hospital S Marta University of Catania, Italy; 3Pediatric Unit, Department of Pediatric Hospital Civile, Ragusa, Italy; 4Department of Neurology, University of Catania, Italy; 5Department of Neurology, Morristown Memorial Hospital, New Jersey, USA; 6Pediatric Unit, Department of Pediatric and Pediatric Neurology, University of Catania, Italy Aim and scope: We conducted this study to estimate the incidence of hyperbilirubinemia in a small neonatal care unit in Catania, Italy, and to determine the underlying causes, which would be of value in identifying and implementing strategies to prevent morbidity from this condition.Background: Management of hyperbilirubinemia remains a challenge for neonatal medicine because of the risk for serious neurological complications related to the toxicity of bilirubin. Methods: From January 2006 to January 2007, we screened 525 newborns born at the Neonatal Care Unit of Valsalva Hospital in Catania, Italy. Infants aged 3–5 days and with unconjugated hyperbilirubinemia were included for assessment if they had a peak serum total bilirubin level exceeding 6 mg/dl (102 μmol/L). Sex, birth weight, gestational age, breast feeding, type of birth, presence of facial bruising (including cephalohematoma) and ABO group were noted. Patients with Toxoplasma or Cytomegalovirus infection, hepatic insufficiency, or suspected drug-induced hyperbilirubinemia were excluded from more detailed analysis.Results: Our year-long nursery sample examined otherwise healthy-appearing term infants for the prevalence of hyperbilirubinemia (defined as bilirubin levels exceeding 6 mg/dL [11mol/L]). We found hyperbilirubinemia in 19% (100/525). Among the patients with hyperbilirubinemia, almost all (99%) had peak levels of bilirubin < 20 mg/dL, levels which are generally considered to be potentially neurotoxic.Conclusions: In our clinic experience, hyperbilirubinemia was generally a serious medical issue and one whose etiology can usually be well defined. Keywords: hyperbilirubinemia, newborns, incidence, breastfeeding